Legal Status of the Court Administration - V. I. Teremetskyi; K. D. Kutsenko (Bulletin of Kharkiv National University of Internal Affairs)
The problems of the legal status of the court administration have been studied. The authors have accomplished analysis of scientific works, the authors of which studied specific features of the legal status of the court administration. It has been stated that the legal status of the court administration is determined by legislative acts and bylaws of Ukraine. The authors have suggested own definition of the legal status of the court administration. The legal status of the court administration is a list of rights, responsibilities and powers of the court administration established by law norms, which is determined by the tasks assigned to the organizational provision of the court and the administration of justice.